ANALISIS KESIAPAN RUMAH SAKIT UMUM TARUTUNG TAPANULI UTARA DALAM PELAKSANAAN KEBIJAKAN JAMINAN KESEHATAN NASIONAL TAHUN 2018 - BENRI SITUMORANG (LP2MTBM MAKARIOZ, 2019)
Implementation of Law No. 40 of 2004 concerning the National Social Security System (SJSN) and Law No. 24 of 2011 concerning the Social Security Organizing Body (BPJS) required thorough preparedness by the organizers of the Health Insurance namely Hospital. Tarutung General Hospital is one of the hospitals that organizes National Health Insurance services.This study aims to determine the readiness of Tarutung General Hospital in the Implementation of Implementation of the National Health Insurance Policy in 2018. This study used a qualitative method with ten informants. Informants in this study were people who were considered appropriate and understood about the readiness to implement a health insurance program. Data collection is done by interview, observation, and documentation.The results showed that for the socialization the Tarutung General Hospital and the BPJS of the Tarutung City branch had been conducted, for the aspect of health facilities there was no readiness because medical devices were still lacking, for Human Resources classified as quantity and quality, the disposition of implementing health services at the General Hospital Tarutung is quite good, for the structure of the hospital bureaucracy with BPJS it has coordinated well. The conclusion of this study is the lack of readiness of Tarutung Hospital in terms of the readiness of health facilities in the implementation of the National Health Insurance program. It is recommended that health facilities at Tarutung General Hospital to complement and improve infrastructure facilities, the government pay more attention to the implementation of the JKN program, as well as more optimized socialization to the community.